2014
DOI: 10.4172/2155-6156.1000378
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Diabetes Knowledge and its Associated Factors among Type 2 Diabetic Patients in Mekelle and Ayder Referral Hospitals, Ethiopia

Abstract: Background: Poor patient understanding of diabetes is believed to impede appropriate self-care management, thus accelerating cardiovascular complications, stroke, and kidney failure. Objective:To assess diabetes knowledge level and associated factors among type 2 diabetic patients in Mekelle hospital and Ayder referral hospitals, Mekelle City, Tigray, Northern Ethiopia.Method: Institutional based cross sectional method was used and 310 study subjects was selected using systematic random sampling technique and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 22 publications
(23 reference statements)
10
40
3
Order By: Relevance
“…Respondents aged 35-44 were 13.4 times more likely to practice self-care activities as compared to those above the age of 64 (Tables 5 and 6). …”
Section: Medication Adherence Based On Mmas-8mentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents aged 35-44 were 13.4 times more likely to practice self-care activities as compared to those above the age of 64 (Tables 5 and 6). …”
Section: Medication Adherence Based On Mmas-8mentioning
confidence: 99%
“…In study conducted in Nigeria to evaluate the level of knowledge among type 2 diabetics showed that knowledge is below mean score 39% ± 16.7% [62]. In a South African primary care setting, showed lower levels of diabetes knowledge with an average of 52.2% compared to their Indian counterparts with an average of 75.9% [63,64].…”
Section: Idf Atlasmentioning
confidence: 99%
“…Awareness of diabetes and health-seeking behavior among the community can assist in early detection of the disease, help to assess their risks, motivate them to seek proper treatment and care, inspire them to take charge of their disease for their lifetime, and in turn, reduce the incidence of complications. [6,7] India with a varied social, economic, cultural, and educational background have a people surrounded with myths and beliefs regarding diseases. Studies have shown that there is still an inadequate awareness about various aspects of diabetes among the general public and also there is also a lack of knowledge and awareness about the existing interventions in prevention and management of its complications.…”
Section: Introductionmentioning
confidence: 99%
“…Similar study was conducted in Ethiopia shows that 57.7% were male, 69% were in the age group of 40-69 years, 34.3% were unemployed, 57% had low monthly income, and all subjects are under control measures such as OHA (41.3%) and insulin (58.7%) [14].…”
Section: Discussionmentioning
confidence: 83%